Oral Communication Skills Included In Sciences Book For The Basic Fourth Class - Zmourod, Amira; Sultan, Manal Ahmed; Jmal, Mohammad Sameer (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research aims to identify to what extent Included Oral Communication Skills In Sciences Book from the Schools' teachers point of view in Lattakia city, and to analyzing the basic fourth class to knew the oral communication skills which are included in it and the sub skills ( listening and talking skills) and it included (56) oral communication skills distributed to (30) skills for talking and (26) for listening and the researcher depended in his analysis for the results on the descriptive curriculum and used content analysis to reach the most importune main and secondary oral communication skills included in the basic fourth class in the Syrian Arab republic for the year 2018-2019. The research ended up with the following results that the degree Included Oral Communication Skills In Sciences Book from the Schools' teachers point of view in Lattakia city was middle degree, and the content analysis results indicated to the incompatibility in distributing the repetitions on the oral communication skills contained within the biology book of the fourth grade. The sample of the content analysis showed that the four communication skill in the analyst is not compatible in distributing the researcher on skill of listing and taking founded fourth class. In the light of the result which they reached important of them: concentrating an oral communication skills which include science curriculum listening and talking skills which will help students to improve the standers of their studies. هدف البحث إلى تعرف مدى تضمين مهارات التواصل الشفوي في كتاب العلوم للصف الرابع الأساسي من وجهة نظر معلمي العلوم، وإلى تحليل مضمون كتاب العلوم للصف الرابع الأساسي لتعرّف مدى تضمنه لمهارات التواصل الشفوي (مهارة الاستماع، مهارة التحدث). وقد اعتمد الباحث أسلوب تحليل المضمون من المنهج الوصفي، أما عينة البحث فكانت (68) مدرس علوم، إضافة إلى كتاب العلوم للفصل الثاني، والذي يحتوي ثلاث وحدات فقط، والمقرر للصف الرابع الأساسي من وزارة التربية السورية للعام الدراسي 2018/ 2019 وكانت أداة البحث استمارة تحليل لمهارات التواصل الشفوي, بناءً على قائمة أعدها الباحث تضمنت (56) مهارة تواصل شفوي موزعة إلى (30) مهارة للتحدث، (26) مهارة للاستماع. توصل الباحث إلى النتائج الآتية: إن درجة تضمين مهارات التواصل الشفوي في كتاب العلوم للصف الرابع الأساسي من وجهة نظر معلمي العلوم جاءت بدرجة متوسطة، كما أتت مهارات التواصل الشفوي بدرجة منخفضة في كتاب العلوم وغير متوافقة في توزيع التكرارات على قائمة التحليل مهارات التواصل الشفوي المتواجدة في كتاب العلوم للصف الرابع الأساسي، وكذلك عدم توافق مهارات الاستماع والتحدث في توزيع التكرارات على مهارات الاستماع والتحدث المتواجدة في كتاب العلوم للصف الرابع الأساسي حيث إن أربع مهارات وردة بدرجة متوسطة وبقية المهارات وردت بدرجة ضعيفة. وفي ضوء نتائج البحث، اقترح الباحث ضرورة الاهتمام بمهارات التواصل الشفوي بشكل أكبر, وتضمينها في مناهج العلوم.